Resin composition, molded product, multilayer structure, and method for producing resin composition

By adding bio-based polyolefins and higher fatty acid metal salts to the resin composition, the problem of degradation of EVOH and polyolefins under thermal history is solved, and better thermal stability and color suppression effect are achieved, and it is suitable for multi-layer structures and molded bodies.

JP2025018666APending Publication Date: 2025-02-06MITSUBISHI CHEM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023122591
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

The existing resin compositions have problems with physical properties and thermal stability after undergoing thermal history, especially when containing EVOH and polyolefins, which are susceptible to thermal history and lead to mass degradation.

Method used

By introducing biopolyolefin and metal salt-based higher fatty acids into the resin composition, a resin composition containing polyolefin resin, EVOH, biopolyolefin and higher fatty acid metal salts is formed, and the composition ratio and additive use are optimized to improve thermal stability and color suppression effect.

Benefits of technology

The resin composition maintains good physical properties and color stability at high temperatures, and is suitable for multi-layer structures and molded bodies, especially when using recycled resins, and avoids mass degradation due to thermal history.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018666000001
    Figure 2025018666000001
Patent Text Reader

Abstract

To provide a resin composition containing a polyolefin resin and an ethylene-vinyl alcoholic copolymer, characterized by superior thermal stability and color inhibition.SOLUTION: A resin composition contains a polyolefin resin (A), an ethylene-vinyl alcoholic copolymer (B), a biopolyolefin resin (C), and a hydrotalcite (D) and / or a higher fatty acid metal salt (E).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a polyolefin resin, an ethylene-vinyl alcohol copolymer (hereinafter referred to as "EVOH"), and hydrotalcites and / or a metal salt of a higher fatty acid. The present invention also relates to a molded article made of the resin composition, a multilayer structure having a layer containing the resin composition, and a method for producing the resin composition. [Background technology]

[0002] Conventionally, EVOH has been mainly used as a food packaging material because of its excellent gas barrier properties and transparency. Although the sheets, films, etc. used as the food packaging material can be produced using the above-mentioned EVOH alone, they are used in the form of a multilayer structure in which other thermoplastic resins are blended to improve physical properties, etc., or layers made of polyolefin resins, etc. are laminated to impart other functions.

[0003] Recently, in order to reduce the environmental load, used resin products, resin scraps and ends generated during the manufacturing process of resin products, and defective products have been collected and recycled into resin compositions containing EVOH and polyolefins.

[0004] However, when a resin composition containing EVOH or polyolefin is repeatedly melt-molded, there is a problem that the quality of the resin composition deteriorates due to the influence of thermal history. In view of this, a resin composition that is not easily affected by repeated thermal history has been proposed, for example, a resin composition containing a polyolefin resin (A), EVOH (B), a hydrotalcite compound (C), a specified higher fatty acid (D), etc. (see Patent Document 1 below). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-278952 Summary of the Invention [Problem to be solved by the invention]

[0006] Although the above resin composition is resistant to the effects of generation of foreign matter and reduction in strength even when repeatedly subjected to thermal history, further improvement in thermal stability is required.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a resin composition which is excellent in thermal stability and whose physical properties are only slightly affected even when subjected to thermal history. [Means for solving the problem]

[0008] However, as a result of intensive research conducted by the present inventors to address the above-mentioned problems, they discovered that the above-mentioned problems can be resolved by further incorporating a bio-polyolefin resin in a resin composition containing EVOH and polyolefin.

[0009] That is, the present invention has the following aspects. [1] A resin composition containing a polyolefin resin (A), an EVOH (B), a biopolyolefin resin (C), and hydrotalcites (D) and / or a metal salt of a higher fatty acid (E). [2] The resin composition according to [1], wherein the biopolyolefin-based resin (C) is a biopolyethylene-based resin. [3] The resin composition according to [1] or [2], wherein the content of the biopolyolefin resin (C) in the entire resin composition is 0.02 to 35 mass %. [4] The resin composition according to any one of [1] to [3], wherein the higher fatty acid metal salt (E) is at least one of a higher fatty acid calcium salt, a higher fatty acid magnesium salt, and a higher fatty acid zinc salt. [5] The resin composition according to any one of [1] to [4], wherein the higher fatty acid metal salt (E) is a higher fatty acid metal salt having 14 to 22 carbon atoms. [6] A molded article comprising the resin composition according to any one of [1] to [5]. [7] A multilayer structure having a layer containing the resin composition according to any one of [1] to [5]. [8] A method for producing a resin composition, comprising the steps of mixing a polyolefin resin (A), an ethylene-vinyl alcohol copolymer (B), a biopolyolefin resin (C), and hydrotalcites (D) and / or a metal salt of a higher fatty acid (E). Effect of the Invention

[0010] The resin composition of the present invention is a resin composition containing a polyolefin resin and EVOH, and yet has superior thermal stability and coloration suppression properties compared to conventional resin compositions. Therefore, the resin composition of the present invention can be suitably used as a raw material for molded articles and multilayer structures having excellent thermal stability and coloration suppression properties. Furthermore, the resin composition of the present invention is particularly suitable when it is a recycled resin composition in which the polyolefin resin and EVOH are made from recovered used resin products or resin scraps discarded during the manufacturing process, because the composition does not deteriorate due to heat and maintains a certain level of quality.

[0011] The reason why the resin composition of the present invention has excellent thermal stability and coloring suppression is that it contains carbon 14 ( 14 It is believed that bio-polyolefin resins containing C) have stronger bond energy due to the primary isotope effect compared to petroleum-derived polyolefin resins that do not contain carbon-14, which slows down decomposition and improves thermal stability and color inhibition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in more detail below based on embodiments of the present invention, but the present invention is not limited to the following embodiments.

[0013] In the present invention, when the expression "x to y" (x and y are arbitrary numbers) is used, unless otherwise specified, it includes not only the meaning of "x or more and y or less", but also the meaning of "preferably greater than x" or "preferably smaller than y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "it is preferably greater than X" or "it is preferably less than Y". Furthermore, "X and / or Y (X and Y are optional)" means at least one of X and Y, and means the following three cases: X only, Y only, and X and Y.

[0014] A resin composition according to one embodiment of the present invention (hereinafter referred to as "the resin composition") contains a polyolefin resin (A), EVOH (B), a biopolyolefin resin (C), and hydrotalcites (D) and / or a metal salt of a higher fatty acid (E). Each component will be described below.

[0015] <Polyolefin resin (A)> Examples of the polyolefin resin (A) used in the present resin composition include polyethylenes such as linear low density polyethylene (LLDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), medium density polyethylene (MDPE), and high density polyethylene (HDPE); polypropylene (PP); ethylene-vinyl acetate copolymer (EVA); ionomers, ethylene-propylene (block or random) copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, ethylene-methacrylic acid copolymers, ethylene-methacrylic acid ester copolymers, propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, polybutene, polypentene, polymethylpentene, and other olefin homopolymers or copolymers, or blends thereof. These may be used alone or in combination of two or more kinds. Among them, polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-propylene (block or random) copolymer, polypropylene (PP) and blends thereof are preferred in terms of economic efficiency and mechanical properties, and polyethylene, polypropylene (PP) and ethylene-propylene (block or random) copolymer are particularly preferred because they provide particularly excellent effects for the present invention.

[0016] The melt flow rate (MFR) (230° C., load 2160 g) of the polyolefin resin (A) is usually from 0.1 to 50 g / 10 min, and preferably from about 0.5 to 30 g / 10 min.

[0017] The polyolefin resin (A) may contain additives such as known plasticizers, lubricants, heat stabilizers, light stabilizers, UV absorbers, antioxidants, crystal nucleating agents, colorants, antistatic agents, surfactants, antibacterial agents, desiccants, oxygen absorbers, and antiblocking agents within a range that does not impair the effects of the present invention (for example, less than 30 mass % based on the total polyolefin resin (A)), and may also be blended with other polyolefin resins.

[0018] The content of the polyolefin resin (A) in the resin composition is usually 40 to 99.99 mass%, preferably 45 to 99.9 mass%, more preferably 50 to 99 mass%, and further preferably 65 to 95 mass%, based on the total mass of the resin composition. When the polyolefin resin (A) is within the above range, the excellent effects of the present invention can be sufficiently obtained.

[0019] <EVOH(B)> The EVOH (B) used in the present resin composition is a resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and a vinyl ester monomer, and is a water-insoluble thermoplastic resin. As the vinyl ester monomer, vinyl acetate is generally used from an economical point of view.

[0020] The polymerization of ethylene and vinyl ester monomers can be carried out by any known polymerization method, such as solution polymerization, suspension polymerization, or emulsion polymerization, and generally, solution polymerization using methanol as a solvent is used. The saponification of the obtained ethylene-vinyl ester copolymer can also be carried out by a known method.

[0021] The EVOH (B) produced in this manner is mainly composed of structural units derived from ethylene and vinyl alcohol structural units, and usually contains a small amount of vinyl ester structural units that remain unsaponified.

[0022] As the vinyl ester monomer, vinyl acetate is typically used because of its good market availability and efficiency in treating impurities during production. Other vinyl ester monomers include, for example, aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate, and aliphatic vinyl esters having usually 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and particularly preferably 4 to 7 carbon atoms can be used. These can be used alone or in combination of two or more kinds.

[0023] The ethylene content in the EVOH (B) can be controlled by the ethylene pressure when copolymerizing the vinyl ester monomer with ethylene, and is 20 to 60 mol%, preferably 25 to 50 mol%, and particularly preferably 25 to 35 mol%. If the content is too low, the gas barrier properties and melt moldability under high humidity conditions tend to decrease, and conversely, if the content is too high, the gas barrier properties tend to decrease. The ethylene content can be measured based on ISO14663.

[0024] The degree of saponification of the vinyl ester component in EVOH (B) can be controlled by the amount, temperature, time, etc. of the saponification catalyst (usually an alkaline catalyst such as sodium hydroxide is used) used when saponifying the ethylene-vinyl ester copolymer, and is usually 90 to 100 mol%, preferably 95 to 100 mol%, particularly preferably 99 to 100 mol%. If the degree of saponification is too low, the gas barrier properties, thermal stability, moisture resistance, etc. tend to decrease. The degree of saponification of the EVOH can be measured based on JIS K6726 (wherein the EVOH is used as a solution uniformly dissolved in a water / methanol solvent).

[0025] The melt flow rate (MFR) of the EVOH (B) (210°C, load 2160 g) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 3 to 35 g / 10 min. If the MFR is too high, the film formability tends to be unstable, whereas if the MFR is too low, the viscosity tends to be too high, making melt extrusion difficult. The MFR is an index of the degree of polymerization of EVOH, and can be adjusted by the amount of polymerization initiator and the amount of solvent used when copolymerizing ethylene with a vinyl ester monomer.

[0026] In addition, EVOH (B) may further contain structural units derived from the comonomers shown below within a range that does not impair the effects of the present invention (for example, 10 mol % or less based on the total EVOH). Examples of the comonomer include olefins such as propylene, 1-butene, and isobutene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 3-butene-1,2-diol, 4-penten-1-ol, and 5-hexene-1,2-diol, as well as their esterified and acylated derivatives; hydroxyalkylvinylidenes such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, 1,3-dibutyryloyloxy-2-methylenepropane, and the like. hydroxyalkylvinylidene diacetates such as hydroxy-2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, or their salts or mono- or dialkyl esters in which the alkyl group has 1 to 18 carbon atoms; acrylic acids such as acrylamide, N-alkylacrylamide in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its acid salts or its quaternary salts. acrylamides; methacrylamide, N-alkyl methacrylamides in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethyl methacrylamide, 2-methacrylamidopropanesulfonic acid or its salt, methacrylamidepropyldimethylamine or its acid salt or its quaternary salt; N-vinyl amides such as N-vinylpyrrolidone, N-vinylformamide, and N-vinylacetamide; vinyl cyanides such as acrylonitrile and methacrylonitrile; alkyl vinyl ethers in which the alkyl group has 1 to 18 carbon atoms, hydroxyl Examples of suitable monomers include vinyl ethers such as dialkyl vinyl ether and alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; and comonomers such as trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride and acrylamido-2-methylpropanesulfonic acid.These can be used alone or in combination of two or more.

[0027] In particular, EVOH having a primary hydroxyl group in the side chain is preferred because it has good secondary formability while maintaining gas barrier properties. Among these, EVOH copolymerized with hydroxyl group-containing α-olefins is preferred, and EVOH having a 1,2-diol structure in the side chain is particularly preferred. In particular, in the case of EVOH having a primary hydroxyl group in the side chain, the content of structural units derived from a monomer having the primary hydroxyl group is usually 0.1 to 20 mol %, preferably 0.5 to 15 mol %, and particularly preferably 1 to 10 mol % of the EVOH.

[0028] The EVOH (B) may be one that has been "post-modified" by, for example, urethanization, acetalization, cyanoethylation, or oxyalkylenation.

[0029] Furthermore, the EVOH (B) may be a mixture of two or more kinds of EVOH, for example, EVOHs having different degrees of saponification, different degrees of polymerization, different copolymerization components, and the like.

[0030] The content of the EVOH (B) in the present resin composition is usually 0.1 to 30 mass%, preferably 0.3 to 25 mass%, more preferably 0.4 to 23 mass%, and further preferably 0.5 to 20 mass%, based on the total mass of the resin composition. When the EVOH (B) is within the above range, the excellent effects of the present invention can be fully exhibited.

[0031] <Bio-polyolefin resin (C)> The "biopolyolefin resin" of the biopolyolefin resin (C) used in the present resin composition means a polyolefin resin obtained by chemical or biological synthesis using renewable biomass resources as raw materials. Biopolyolefin resins have the characteristic that, even if they are incinerated, they do not increase the carbon dioxide concentration in the atmosphere due to the carbon neutrality of biomass.

[0032] The biopolyolefin resin (C) is preferably a biopolyolefin derived from a bioalcohol obtained from a plant raw material, that is, the biopolyolefin resin (C) is preferably a plant-derived polyolefin resin.

[0033] In addition, polyolefin resins derived from plants (biomass resources) and polyolefin resins derived from petroleum do not differ in physical properties such as molecular weight and mechanical properties. Therefore, the bio-based degree is generally used to distinguish between them. The bio-based degree is defined as the carbon content of petroleum-derived polyolefin resins. 14 Since it does not contain C (radioactive carbon-14, half-life 5730 years), 14 The concentration of C is measured by accelerator mass spectrometry and used as an index of the content of plant-derived bio-polyolefin resin. Therefore, if a film uses plant-derived polyolefin resin, measuring the bio-based content of the film will give a bio-based content that corresponds to the content of plant-derived polyolefin resin. In other words, bio-polyolefin resin (C) is a material that can detect radioactive carbon ( 14 C).

[0034] The bio-based content can be measured, for example, by the following method. The sample to be measured is burned to generate carbon dioxide, which is purified in a vacuum line and reduced with hydrogen using iron as a catalyst to generate graphite. The graphite is then subjected to a tandem accelerator-based 14 Attach it to the C-AMS dedicated device (manufactured by NEC) 14 Counting C, 13 Concentration of C ( 13 C / 12 C). 14 Concentration of C ( 14 C / 12 C), and from this measurement, the carbon content of the sample relative to the standard modern carbon is 14 Calculate the percentage of C concentration.

[0035] The bio-based content of the bio-polyolefin resin (C) used in the present resin composition is usually 1 to 99%, preferably 5 to 95%, and particularly preferably 10 to 90%. By setting the bio-based content of the bio-polyolefin resin (C) within the above range, a resin composition having better thermal stability can be obtained.

[0036] The polyolefin resin used in the biopolyolefin resin (C) is not particularly different from the polyolefin of the polyolefin resin (A) described above, and examples thereof include polyethylenes such as linear low density polyethylene (LLDPE), low density polyethylene (LDPE), very low density polyethylene (VLDPE), medium density polyethylene (MDPE), and high density polyethylene (HDPE), ethylene-vinyl acetate copolymers (EVA), ionomers, ethylene-propylene (block or random) copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, ethylene-methacrylic acid copolymers, ethylene-methacrylic acid ester copolymers, propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, polybutene, polypentene, polymethylpentene, and other olefin homopolymers or copolymers, or blends thereof. These may be used alone or in combination of two or more kinds. Among them, polyethylene, ethylene-vinyl acetate copolymer (EVA), ethylene-propylene (block or random) copolymer, and blends thereof are preferred in terms of economic efficiency and mechanical properties, and polyethylene and ethylene-propylene (block or random) copolymer are particularly preferred, since they further suppress discoloration due to heating of the recycled resin composition.

[0037] The melt flow rate (MFR) (190° C., load 2160 g) of the biopolyolefin resin (C) is usually 0.1 to 50 g / 10 min, and more preferably about 0.5 to 30 g / 10 min.

[0038] Examples of commercially available biopolyolefin resins (C) suitably used in the present invention include Green PE (LDPE) manufactured by Braskem, which is biopolyethylene.

[0039] The content of the above biopolyolefin resin (C) in the resin composition is usually 0.02 to 35% by mass, preferably 0.5 to 30% by mass, more preferably 0.8 to 15% by mass, and still more preferably 1.0 to 10% by mass, based on the total resin composition. By setting the content of the biopolyolefin resin (C) within the above range, a resin composition with more excellent thermal stability can be obtained.

[0040] <Hydrotalcites (D)> Examples of the hydrotalcites (D) used in the present resin composition include hydrotalcite-based solid solutions represented by the following general formula (1).

[0041] [Chemical formula 1] [(M1 2+ ) y1 (M2 2+ ) y2 1-x M x 3+ (OH)2A n- x / n ·mH2O ……(1) [In the formula, M1 2+ is at least one metal selected from Mg, Ca, Sr, and Ba, M2 2+ is at least one metal selected from Zn, Cd, Pb, and Sn, M x 3+ is a trivalent metal, A n- is an n-valent anion, and x, y1, y2, and m are positive numbers represented by 0 < x ≤ 0.5, 0.5 < y1 < 1, y1 + y2 = 1, and 0 ≤ m < 2, respectively.]

[0042] In the above general formula (1), M1 2+ is preferably Mg or Ca, and M2 2+ is preferably Zn or Cd. Further, M x 3+Examples of the elements include Al, Bi, In, Sb, B, Ga, and Ti, which may be used alone or in combination of two or more. Among these, Al is most practical. n- For example, CO3 2- ,OH - ,HCO3 - , salicylate ion, citrate ion, tartrate ion, NO3 - ,I - ,(OOC-COO) 2- ,ClO 4- ,CH3COO - ,CO3 2- ,(OOCHC=CHCOO) 2- ,〔Fe(CN)6〕 4- These can be used alone or in combination of two or more kinds. Among them, CO3 2- OH - is particularly useful.

[0043] As a specific example of the hydrotalcite-based solid solution, [Mg 0.75 Zinc 0.25 ] 0.67 Al 0.33 (OH)2(CO3) 0.165 0.45H2O, [Mg 0.79 Zinc 0.21 ] 0.7 Al 0.3 (OH)2(CO3) 0.15 , [Mg 1 / 7 Ca 3 / 7 Zinc 3 / 7 ] 0.7 Al 0.3 (OH)2(OOCHC=CHCOO) 0.15 0.41H2O, [Mg 6 / 7 CD 1 / 7 ] 0.7 Al 0.3 (OH)2(CH3COO) 0.3 0.34H2O, [Mg 5 / 7 Pd 2 / 7 ] 0.7 Al 0.30 (OH)2(CO3) 0.15 0.52H2O, [Mg 0.74 Zinc 0.26 ]0.68 Al 0.32 (OH)2(CO3) 0.16 , [Mg 0.56 Zinc 0.44 ] 0.68 Al 0.32 (OH)2(CO3) 0.16 0.2H2O, [Mg 0.81 Zinc 0.19 ] 0.74 Al 0.26 (OH)2(CO3) 0.13 , [Mg 0.75 Zinc 0.25 ] 0.8 Al 0.20 (OH)2(CO3) 0.10 0.16H2O, [Mg 0.71 Zinc 0.29 ] 0.7 Al 0.30 (OH)2(NO3) 0.30 , [Mg 0.71 Zinc 0.29 ] 0.7 Al 0.30 (OH)2(OOCHC=CHCOO) 0.15 , [Mg 0.14 Ca 0.57 Zinc 0.28 ] 0.7 Al 0.30 (OH) 2.3 0.25H2O, among which [Mg 0.75 Zinc 0.25 ] 0.67 Al 0.33 (OH)2(CO3) 0.165 0.45H2O, [Mg 0.79 Zinc 0.21 ] 0.7 Al 0.3 (OH)2(CO3) 0.15 , [Mg 6 / 7 CD 1 / 7 ] 0.7 Al 0.3 (OH)2(CH3COO) 0.3 0.34H2O, [Mg 5 / 7 Pd 2 / 7 ] 0.7 Al 0.30 (OH))2(CO3) 0.15 0.52H2O etc.

[0044] Other examples of the hydrotalcites (D) include compounds represented by the following general formula (2).

[0045] [C2] M x Al y (OH) 2x+3y-2z (E) z aH2O ……(2) [In the formula, M is Mg, Ca, or Zn, E is CO3 or HPO4, x, y, and z are positive numbers, and a is 0 or a positive number.]

[0046] Specific examples of the compound represented by the above general formula (2) include Mg 4.5 Al2(OH) 13 CO3·3.5H2O, Mg5Al2(OH) 14 CO3·4H2O,Mg6Al2(OH) 16 CO3·4H2O, Mg8Al2(OH) 20 CO3·5H2O,Mg 10 Al2(OH) 22 (CO3)2·4H2O, Mg6Al2(OH) 16 HPO4·4H2O, Ca6Al2(OH) 16 CO3·4H2O, Zn6Al6(OH) 16 CO3·4H2O, etc. In addition, the same effect can be expected even if the chemical formula is not clearly indicated, for example, a part of OH in Mg2Al(OH)9·3H2O is replaced with CO3 or HPO4, or even if the crystal water is removed (a=0). In particular, among these, a compound in which M is Mg and E is CO3 is preferably used because it effectively suppresses deterioration of appearance due to coloring caused by phase separation and phase-separated foreign matter (so-called eye jerk) caused by phase separation, as well as molding stability.

[0047] The particle size of the hydrotalcites (D) is, for example, usually 10 μm or less, more preferably 5 μm or less, and particularly preferably 1 μm or less. That is, if the average particle size is too large, the effect of the present invention tends not to be fully obtained. The average particle size referred to here is a value measured by the LUZEX method.

[0048] Among the above hydrotalcites (D), it is particularly preferable to use the hydrotalcite-based solid solution represented by the general formula (1) above, because of its high molding stability, phase separation foreign matter (dye deposits) suppression effect, and coloration suppression effect.

[0049] When the hydrotalcites (D) are used, the content is usually 0.001 to 30 mass%, preferably 0.005 to 25 mass%, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 5 mass% based on the total mass of the resin composition. If the content is too low, molding stability and the effect of suppressing foreign matter and coloring tend not to be sufficiently obtained. On the other hand, if the content is too high, the appearance of the obtained molded product tends to deteriorate, and the effect of suppressing coloring and mechanical properties tend to decrease.

[0050] <Higher fatty acid metal salts (E)> Examples of the higher fatty acid metal salt (E) used in the present resin composition include metal salts of organic acids having 8 or more carbon atoms (more preferably 12 to 30 carbon atoms, particularly preferably 14 to 22 carbon atoms), such as alkali metal salts of lithium, sodium, potassium, etc.; alkaline earth metal salts of magnesium, calcium, barium, etc.; and transition metal salts of zinc, copper, cobalt, iron, manganese, etc. Among these, from the viewpoints of molding stability and the effect of suppressing phase-separated foreign matter (eye plug) and coloration, alkaline earth metal salts and transition metal salts of higher fatty acids having 14 to 22 carbon atoms are preferred, and magnesium, calcium, and zinc salts of stearic acid, hydroxystearic acid, oleic acid, and lauric acid are particularly preferred.

[0051] When the higher fatty acid metal salt (E) is used, its content is usually 0.001 to 30 mass% based on the total mass of the resin composition, preferably 0.005 to 25 mass%, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 5 mass%. If the content is too low, molding stability and the effect of suppressing foreign matter and coloring tend not to be sufficiently obtained. On the other hand, if the content is too high, the appearance of the obtained molded product tends to deteriorate, and the effect of suppressing coloring and mechanical properties tend to decrease.

[0052] The hydrotalcites (D) and the higher fatty acid metal salts (E) may be used either alone or in combination. When both are used in combination, the respective contents are preferably within the above ranges.

[0053] <Titanium compounds (F)> In the present resin composition, a titanium compound (F) can be used together with the above essential components. Examples of the titanium compound (F) include inorganic titanium compounds and organic titanium compounds. The titanium compounds may be used alone or in combination of two or more. Among them, inorganic titanium compounds are preferred.

[0054] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium. Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium suboxide. Examples of the titanium hydroxide include titanium(I) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(I) chloride and titanium(II) chloride. Examples of the inorganic salts of titanium include titanium phosphate and titanium sulfate. Among these, titanium oxide is preferred, titanium(IV) oxide is more preferred, and rutile-type titanium(IV) oxide is particularly preferred.

[0055] Examples of the organic titanium compound include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.

[0056] In addition, the above titanium compound (F) may be present in the resin composition as a titanium compound, or may be present in an ionized state or in the form of a complex interacting with a resin component or other ligands.

[0057] When the titanium compound (F) is used, its average particle size is usually 0.001 to 100 μm, preferably 0.01 to 50 μm, and more preferably 0.015 to 20 μm.

[0058] When the titanium compound (F) is used, the content thereof calculated as metal is preferably 0.001 to 250,000 ppm, more preferably 0.01 to 200,000 ppm, still more preferably 0.1 to 100,000 ppm, and particularly preferably 1 to 50,000 ppm, based on mass of the entire resin composition.

[0059] The metal-equivalent content of the titanium compound (F) can be quantified by weighing the resin composition into a platinum crucible, incinerating it using a burner and an electric furnace, decomposing the incinerated product by heating with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution obtained by constant volume measurement using an ICP mass spectrometer (Agilent 8800, manufactured by Agilent Technologies).

[0060] <Other ingredients> In addition to the essential components polyolefin resin (A), EVOH (B), biopolyolefin resin (C), hydrotalcites (D) and / or higher fatty acid metal salt (E), and titanium compound (F), which can be used as appropriate, other types of resins and optional additives (hereinafter, these are referred to as "other components") can be blended into the resin composition according to various purposes within a range that does not significantly impair the effects of the present invention. Only one type of other component may be used, or two or more types may be used in any combination and ratio.

[0061] Examples of the additives include antioxidants, ultraviolet absorbers, plasticizers, lubricants, fillers, and antistatic agents.

[0062] When the present resin composition contains the above-mentioned "other components", the total content thereof is usually 30 mass % or less, preferably 20 mass % or less, and more preferably 10 mass % or less, relative to the present resin composition.

[0063] [Method of producing resin composition] The resin composition can be produced by mixing the essential components, polyolefin resin (A), EVOH (B), biopolyolefin resin (C), hydrotalcites (D) and / or higher fatty acid metal salt (E), titanium compound (F) used as needed, and other components. Examples of the mixing method include known methods such as a dry blend method, a melt mixing method in which a compound is obtained using a single-screw extruder or a twin-screw extruder, a solution mixing method, and an impregnation method, and these can be combined in any desired manner. The polyolefin resin (A) and EVOH (B) can be made of recycled resin obtained by pulverizing recovered scraps of a laminate including a polyolefin resin layer and an EVOH layer.

[0064] [Resin composition] The resin composition thus obtained is less susceptible to decomposition under high temperature heating, has excellent thermal stability, and is also excellent in inhibiting discoloration, compared to conventional resin compositions that do not contain biopolyolefin resins.

[0065] The melt flow rate (MFR) of the present resin composition (230° C., load 2160 g) is usually from 0.1 to 50 g / 10 min, preferably from 0.5 to 30 g / 10 min, and particularly preferably from 2 to 10 g / 10 min.

[0066] The water content of the present resin composition is usually from 0.01 to 0.5% by mass, preferably from 0.02 to 0.35% by mass, and particularly preferably from 0.05 to 0.3% by mass.

[0067] The water content of the resin composition in the present invention is measured and calculated by the following method. The mass (W1) of the resin composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then cooled in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. Moisture content (mass%)=[(W1-W2) / W1]×100

[0068] The present resin composition is prepared as a resin composition in various forms, such as pellets or powder, and is provided as a material for various molded bodies and multilayer structures. As described above, since the present resin composition has excellent thermal stability and coloration suppression properties, a molded body using the present resin composition or a multilayer structure having a layer using the present resin composition has the advantage that deterioration in quality, such as thermal degradation and coloration, is small even when recycled.

[0069] Furthermore, as already described, the polyolefin resin (A) and EVOH (B) in the present resin composition may be derived from recycled materials such as scraps of laminates containing a polyolefin resin layer and an EVOH layer. When the present resin composition is such a recycled resin composition, as described above, deterioration in quality due to heat degradation, coloration, etc. is small, and therefore it is possible to provide molded articles and multilayer structures with excellent quality, which is preferable.

[0070] [Molded body] A molded article according to one embodiment of the present invention (hereinafter, referred to as the present molded article) is obtained by molding the present resin composition.

[0071] Examples of the shape of the present molded product include films, sheets, tapes, cups, trays, tubes, bottles, pipes, filaments, irregular cross-section extrudates, and various irregularly shaped products.

[0072] The molding method for obtaining the molded article is not particularly limited, and any molding method applicable to general resin compositions can be used, such as extrusion molding, blow molding, injection molding, thermoforming, etc.

[0073] [Multilayer structure] A multilayer structure according to one embodiment of the present invention (hereinafter, referred to as "the present multilayer structure") has at least one layer containing the present resin composition. The present multilayer structure can be provided with additional strength or other functions by being laminated with another substrate containing as a main component a thermoplastic resin other than the present resin composition.

[0074] In addition, in the present multilayer structure, the layer containing the present resin composition is preferably a layer (regrind layer) formed using the present resin composition (=recycled resin composition) containing polyolefin resin (A) and EVOH (B) derived from a recovered material obtained by recovering scraps of a laminate containing a polyolefin resin layer and an EVOH layer. Such a multilayer structure having a regrind layer will be described below.

[0075] The recycled laminates containing a polyolefin resin layer and an EVOH layer used to obtain the above-mentioned regrind layer are scraps, unnecessary parts such as ends of the product, defective products, or waste collected during production, or the like after the molded body has been used for various purposes. These recycled materials are reused to prepare the present resin composition, which can be used to obtain the regrind layer.

[0076] In addition, the recovered material used for recycling is generally scraps related to one molded body, but scraps related to two or more types of molded bodies may be used as the recovered material.

[0077] To obtain the regrind layer, for example, the recycled material (a composition containing polyolefin resin (A) and EVOH (B)) is appropriately combined with other components of the resin composition, such as biopolyolefin resin (C), hydrotalcites (D), higher fatty acid metal salt (E), and optional additives, and if necessary, polyolefin resin (A) and EVOH (B) are newly added. These are uniformly mixed to obtain a recycled resin composition for the regrind layer. The above melt molding method will now be described.

[0078] First, in order to subject the recovered laminate to melt molding again using an extruder or the like, it is preferable to pulverize the recovered laminate.

[0079] The above-mentioned recovered material can be pulverized by using a known pulverizer. The shape and particle size of the pulverized product are usually 0.25 to 0.85 g / mL, more preferably 0.3 to 0.7 g / mL, and particularly preferably 0.35 to 0.6 g / mL, as measured in accordance with the "5.3 Apparent Density" test method of JIS-K6891. If the apparent density is too small, the dispersion of EVOH in the regrind layer becomes poor, and the melt moldability and mechanical properties of the regrind layer of the obtained molded product tend to decrease, and if it is too large, the melt moldability of the regrind layer of the obtained molded product tends to decrease due to poor supply in the extruder.

[0080] This apparent density can be controlled by arbitrarily adjusting the shape of the grinding blade of the grinding machine, the rotation speed of the grinding blade, the grinding processing speed, the size of the openings of the mesh used, and the like.

[0081] Here, the content of EVOH in the above-mentioned recovered material is usually 0.1 to 30% by mass based on the total mass of the recovered material, and in order to particularly exhibit the effect of the present resin composition, it is further preferably set to 0.3 to 25% by mass, particularly 0.5 to 20% by mass. In the present invention, the improving effect is exhibited for any recovered material content, but the improving effect is particularly exhibited within the above range.

[0082] The content of EVOH in the above-mentioned recycled material depends on the thickness ratio of the EVOH layer in the laminate, and when the content of EVOH is too low, the content may be adjusted by mixing an appropriate amount of a similar or different unused EVOH as necessary.On the other hand, when the content of EVOH is too high, it is also practically preferable to adjust the content by mixing an appropriate amount of a same or different unused polyolefin resin.

[0083] Next, the remaining components of the resin composition, i.e., the biopolyethylene resin (C), the hydrotalcites (D) and / or the higher fatty acid metal salt (E), are blended with the pulverized recovered material. As the blending method, for example, a known mixing device such as a rocking mixer, a ribbon blender, a super mixer, or a line mixer can be used.

[0084] In this manner, the present resin composition, which is a recycled resin composition containing recycled materials, can be obtained.

[0085] The present resin composition can be used to obtain a present multilayer structure having at least one regrind layer. The present multilayer structure having a regrind layer is generally preferably a multilayer structure containing, in addition to the regrind layer, a polyolefin resin layer, an EVOH layer, and, if necessary, an adhesive resin layer.

[0086] Examples of the layer configuration of the multilayer structure containing a regrind layer include polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer, polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / polyolefin resin layer, polyolefin resin layer / regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / regrind layer / polyolefin resin layer, and further regrind layer / EVOH layer, regrind layer / adhesive resin layer / EVOH layer, regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / EVOH layer, regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / polyolefin resin layer, regrind layer / adhesive resin layer / EVOH layer / adhesive resin layer / regrind layer / polyolefin resin layer, polyolefin resin layer / adhesive resin layer / EVOH layer / regrind layer / EVOH layer / adhesive resin layer / polyolefin resin layer, and the like.

[0087] The thickness of each layer of the multilayer structure containing a regrind layer depends on the layer structure, the type of polyolefin resin, the application, the container form, the required physical properties, etc., and cannot be generally determined, but the regrind layer is usually 5 to 5000 μm, and more preferably 30 to 1000 μm. The EVOH layer is usually 5 to 500 μm, and more preferably 10 to 200 μm. The polyolefin resin layer is usually 5 to 5000 μm, and more preferably 30 to 1000 μm. In this case, when an adhesive resin layer is present, the adhesive resin layer is usually 5 to 400 μm, and more preferably 10 to 150 μm.

[0088] The thickness ratio of the regrind layer to the polyolefin resin layer is usually 1 / 5 to 10 / 1, and preferably 1 / 2 to 5 / 1. The thickness ratio of the regrind layer to the EVOH layer is usually 1 / 1 to 100 / 1, and preferably 5 / 1 to 20 / 1.

[0089] The regrind layer-containing multilayer structure can be molded, for example, by the same method as the method for forming the laminate to be the recycled product. Specifically, it can be manufactured by the following method using the polyolefin resin used in the polyolefin resin layer of the laminate to be the recycled product, the EVOH used in the EVOH layer, the present resin composition, and the adhesive resin used in the adhesive resin layer.

[0090] Examples of methods for obtaining the multilayer structure include a method of melt-extrusion laminating the present resin composition onto an EVOH film, sheet, etc., a method of melt-extrusion laminating the present resin composition onto a substrate consisting of a polyolefin layer, a method of co-extruding the present resin composition with EVOH or a polyolefin resin, and a method of dry laminating a film, sheet, etc. of EVOH or a polyolefin resin with a film, sheet, etc. of the present resin composition using an adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, a polyurethane compound, etc. The melt molding temperature during the above melt extrusion is usually in the range of 150 to 300°C.

[0091] The above-mentioned regrind layer-containing multilayer structure can be used as it is for various shapes, but it can also be subjected to a heat stretching treatment in order to further improve the physical properties of this laminate and to mold it into any desired container shape.

[0092] The heat stretching treatment as used herein means an operation of forming a thermally uniformly heated film, sheet or parison-like multilayer structure into a shape such as a cup, tray, tube or bottle by means of a chuck, plug, vacuum force, compressed air force, blow or the like.

[0093] Examples of the stretching method in the above-mentioned heat stretching treatment include roll stretching, tenter stretching, tubular stretching, stretch blowing, vacuum forming, pressure forming, vacuum pressure forming, etc. In the case of biaxial stretching, either simultaneous biaxial stretching or sequential biaxial stretching can be adopted. The stretching temperature is usually 60 to 170°C, and more preferably about 80 to 160°C. Either uniaxial stretching or biaxial stretching can be used, and the higher the stretching ratio is, the better the physical properties will be, and a stretched molded product with excellent gas barrier properties will be obtained without pinholes, cracks, stretching unevenness, thickness deviation, delamination, etc. during stretching.

[0094] In the present multilayer structure, the recycled material used for the regrind layer may also have a regrind layer therein, and a laminate having at least one regrind layer containing such recycled material can be molded by the same method using the same type of resin as the recycled material as a raw material. That is, a laminate having at least one regrind layer (recycled product) is manufactured using a resin composition obtained from the recycled material, and the recycled material of the molded product may be used again as the regrind layer of a similar laminate (recycled product).

[0095] In addition, as other forms of the present multilayer structure, [1] recycled materials of laminates having multiple different types of polyolefin resin layers or multiple different types of EVOH layers, and / or recycled materials of multiple different types of laminates can be used in the same regrind layer, or [2] recycled materials can be used in the regrind layer of a laminate having a different type of polyolefin resin and EVOH from the polyolefin resin and EVOH contained in the recycled materials.

[0096] In addition, in order to improve moldability, physical properties, and the like, antioxidants, heat stabilizers, light stabilizers, lubricants, antistatic agents, crystal nucleating agents, plasticizers, colorants, UV absorbers, surfactants, antibacterial agents, desiccants, oxygen absorbers, antiblocking agents, slip agents, inorganic or organic fillers, and the like can be added to each layer of the present multilayer structure, provided that the effects of the present invention are not impaired.

[0097] Furthermore, the present multilayer structure may be subjected to processes such as heat treatment, cooling treatment, rolling treatment, printing treatment, dry lamination treatment, solution or melt coating treatment, bag making, deep drawing, box processing, tube processing, and split processing, as required.

[0098] The multilayer structure, whether recycled or re-recycled, is useful as a container for various purposes such as general foods, seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, soups, beverages, cosmetics, medicines, detergents, fragrances, industrial chemicals, pesticides, and fuels, but is particularly useful as bottle-shaped or tube-shaped containers for semi-solid foods and seasonings such as mayonnaise, ketchup, sauces, miso, wasabi, mustard, and sauces for grilled meat, and liquid beverages and seasonings such as salad oil, mirin, sake, beer, wine, juice, black tea, sports drinks, mineral water, and milk; cup-shaped containers for semi-solid foods and seasonings such as fruit, jelly, pudding, yogurt, mayonnaise, miso, processed rice, cooked foods, and soups; and tray-shaped containers for raw meat, processed meat products (ham, bacon, sausages, and the like), cooked rice, and pet food. EXAMPLES

[0099] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In addition, unless otherwise specified, "parts" and "%" below are based on mass. Prior to the examples, the following components were prepared:

[0100] [Polyolefin resin (A1)] Polypropylene (Nippon Polypropylene, Novatec EA9), MFR (230°C, load 2160g) 0.5g / 10min [Adhesive resin] Maleic anhydride grafted ethylene-propylene random copolymer (Mitsubishi Chemical, Modic A), MFR (230°C, load 2160g) 3.2g / 10min [EVOH(B1)] EVOH (prototype, ethylene content 32 mol%, saponification degree 99.9 mol%), MFR (210℃, load 2160g) 3.8g / 10min [Bio-polyolefin resin (C1)] Bio-polyethylene: LDPE (Brakkem, SEB853), MFR (190°C, load 2160g) 2.7g / 10min, bio-based content: 95% or more [Petroleum-derived polyolefin resin (C2)] Petroleum-derived polyethylene: LDPE (Japan Polyethylene Corporation, LF440HB), MFR (190°C, load 2160g) 2.8g / 10min [Hydrotalcites (D1)] Hydrotalcite solid solution (Kyowa Chemical Industry Co., Ltd., ZHT-4A) [Higher fatty acid metal salts (E1)] Calcium stearate (Nissan Calcium Stearate S, manufactured by Nippon Oil & Fats Co., Ltd.)

[0101] <Example 1> A recycled laminate in which a layer made of polyolefin resin (A1) and a layer made of EVOH (B1) are laminated via an adhesive resin layer was pulverized, and the recycled pulverized material was mixed with bio-derived polyethylene (C1), hydrotalcites (D1), and higher fatty acid metal salt (E1) in a ratio such that each component has the composition shown in Table 1 by dry blending, and then fed to a twin-screw kneader at a rate of 8 kg / hour using a mass feeder, and then strand-cut with a drum pelletizer to prepare a pellet-shaped resin composition. The kneading conditions are as follows: [Mixing conditions] Twin screw extruder: Diameter 20mm L / D=48 (Toshiba Machine Co., Ltd.) ·Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 / H=150 / 200 / 220 / 220 / 220 / 220 / 220 Screw speed: 250 rpm - Take-off speed: 12m / min

[0102] <Examples 2 and 3, Comparative Example 1> Resin compositions of Examples 2 and 3 and Comparative Example 1 were prepared in the same manner as in Example 1, except that the types and amounts of each component were changed as shown in Table 1 below.

[0103] The following thermal stability evaluation and coloration inhibition evaluation were carried out using the obtained resin compositions of Examples 1 to 3 and Comparative Example 1. The results are shown in Table 1 below.

[0104] [Thermal stability evaluation] Using 5 mg of the obtained pellet-like resin composition, the temperature at which the resin composition had decreased to 95% of the mass before measurement (5% mass loss temperature) was measured using a thermogravimetric analyzer (Perkin Elmer, Pyris 1 TGA) under conditions of a nitrogen atmosphere, an air flow rate of 20 mL / min, and a temperature range of 30 to 550° C. The higher this value, the slower the decomposition of the resin composition is, and the better the thermal stability of the resin composition is.

[0105] [Coloration suppression evaluation (YI value ratio)] The YI value of the resin composition before heating was measured using a spectrophotometer (manufactured by Nippon Denshoku Industries Co., Ltd.). At this time, the sample was filled into a cylinder with an inner diameter of 32 mm and a height of 30 mm, and the measurement was performed in a state where the sample was completely worn down. In addition, the sample was heated in an oven under an air atmosphere at 60°C for 3 days, and the YI value after heating was measured in the same manner. The ratio of the YI value after heating to the YI value before heating was calculated. The larger this value, the more yellow the resin composition was colored after heating.

[0106] [Table 1]

[0107] From the results in Table 1, it can be seen that the resin compositions of Examples 1 to 3, which used bio-polyethylene (C1) together with the recycled laminate, have improved thermal stability compared to Comparative Example 1, which used petroleum-derived polyethylene (C2). The reason for this is that the carbon-14 ( 14Bio-polyethylene (C1) containing C has stronger bond energy due to the primary isotope effect, which slows decomposition and increases thermal stability, and is thought to provide a synergistic effect with hydrotalcites (D1) and metal salts of higher fatty acids (E1). Furthermore, comparing Example 1 with Comparative Example 1, it is clear that the use of biopolyethylene (C1) rather than petroleum-derived polyethylene (C2) results in better coloration suppression properties. It is also clear that the effects of the products of Examples 1 to 3, that is, excellent thermal stability and coloration inhibition, can be obtained in the same manner even if the blending ratio and types of each component are changed. [Industrial Applicability]

[0108] The resin composition can have higher thermal stability and coloring inhibition than a resin composition using a petroleum-derived polyolefin resin. Therefore, a molded body made of the resin composition and a multilayer structure having a layer containing the resin composition are useful as materials for various packaging containers. In particular, the resin composition is useful as a recycled resin composition using a resin recovery product containing a polyolefin resin and EVOH.

Claims

1. A resin composition containing a polyolefin resin (A), an ethylene-vinyl alcohol copolymer (B), a biopolyolefin resin (C), and a hydrotalcite (D) and / or a metal salt of a higher fatty acid (E).

2. The resin composition according to claim 1, wherein the biopolyolefin resin (C) is a biopolyethylene resin.

3. The resin composition according to claim 1 or 2, wherein the content of the biopolyolefin resin (C) relative to the entire resin composition is 0.02 to 35 mass%.

4. 3. The resin composition according to claim 1, wherein the higher fatty acid metal salt (E) is at least one of a higher fatty acid calcium salt, a higher fatty acid magnesium salt, and a higher fatty acid zinc salt.

5. 3. The resin composition according to claim 1, wherein the higher fatty acid metal salt (E) is a higher fatty acid metal salt having 14 to 22 carbon atoms.

6. A molded article comprising the resin composition according to claim 1 or 2.

7. A multilayer structure having a layer comprising the resin composition according to claim 1 or 2.

8. A method for producing a resin composition, comprising the steps of mixing a polyolefin resin (A), an ethylene-vinyl alcohol copolymer (B), a biopolyolefin resin (C), and a hydrotalcite (D) and / or a metal salt of a higher fatty acid (E).

Citation Information

Patent Citations

  • Resin composition, its production and use

    JP1997278952A